Transvenous Lead Extraction: Work in Progress - Zaki Akhtar; Manav Sohal; Mary N Sheppard; Mark M Gallagher (European Cardiology Review)
Cardiac implantable electronic devices are the cornerstone of cardiac rhythm management, with a significant number of implantations annually. A rising prevalence of cardiac implantable electronic devices coupled with widening indications for device removal has fuelled a demand for transvenous lead extraction (TLE). With advancement of tools and techniques, the safety and efficacy profile of TLE has significantly improved since its inception. Despite these advances, TLE continues to carry risk of significant complications, including a superior vena cava injury and mortality. However, innovative approaches to lead extraction, including the use of the jugular and femoral accesses, offers potential for further gains in safety and efficacy. In this review, the indications and risks of TLE are discussed while examining the evolution of this procedure from simple traction to advanced methodologies, which have contributed to a significant improvement in safety and efficacy.